FACTORS INFLUENCE ENTREPRENEURIAL INTENTION AMONG POLYTECHNIC HULU TERENGGANU’S ACCOUNTING STUDENTS - Suriami Sulaiman; Wan Zurina Nik Abdul Majid; Nurfazilahaini Muhamad Hanafi; Wan Muzlaina Wan Mustafa; Wan Roshaini Wan Ali (Journal of Islamic, Social, Economics and Development, 2024)
This study's primary goal is to examine Diploma Accountancy’s students in Polytechnic Hulu Terengganu entrepreneurial intentions. The study is consistent with the initiative to encourage Malaysian participation in starting a business. As a result, the study used Ajzen's Theory of Planned Behaviour from 1991 to pinpoint the variables that affect Diploma Accountancy’s students in Polytechnic Hulu Terengganu entrepreneurial intention. The questionnaire was distributed to all Diploma Accountancy in Polytecnic Hulu Terengganu in the form of google form. There were 100 respondents analysed to test the hypothesis and meet the study's objectives. The results demonstrate a positive relationship between entrepreneurial intention among Diploma Accountancy’s students in Polytechnic Hulu Terengganu only for personal attitudes but not for subjective norms and perceived behavioural control. According to the regression analysis, personal attitudes is the best predictor of entrepreneurial intention. The goal of the study is to support those responsible for promoting entrepreneurial activities, such as polytechnics that want to produce more graduates with a strong interest in entrepreneurship. The study contributes to research scholar, government, as well as entrepreneurship educators since this study provided necessary factors become entrepreneur based on young perspectives. In summation, with the aim of increasing students’ entrepreneurial interest, the results provided by this study are insightful for entrepreneurial higher educational institutions by enhancing and designing the entrepreneurial course offering as to be more proactive enough. This study also contributes to theoretical aspect on the relationship between personal attitudes, subjective norms, perceived behaviour control and entrepreneurial intention.